MACROANEURYSMS ASSOCIATED WITH CONGENITAL RETINAL MACROVESSELS. Issue Volume 14:Issues 1(2020) (2020) - Sebrow, Dov B.; Cunha de Souza, Eduardo; Belúcio Neto, José; Roizenblatt, Marina; Zett Lobos, Claudio; Paulo Bonomo, Pedro; Modi, Yasha; Schuman, Joel S.; Freund, K. Bailey
Abstract : Purpose: Congenital retinal macrovessels are large aberrant retinal blood vessels that cross the horizontal raphe and can traverse the central macula. Using multimodal imaging and optical coherence tomography angiography, we describe 2 cases of congenital retinal macrovessel associated with macroaneurysms. Methods: Two patients presented for evaluation and were found to have congenital retinal macrovessels associated with macroaneurysms. Color photography, optical coherence tomography, fundus autofluorescence fluorescein angiography, and optical coherence tomography angiography were performed and used to establish the diagnosis and monitor resolution at follow-up visits. Results: The first patient presented with central vision loss in the right eye and was noted to have a ruptured macroaneurysm and scattered microaneurysms along the course of a venous macrovessel. After 3 months of observation, the patient's vision improved. The second patient presented for evaluation of a cataract in her left eye and was incidentally found to have an arterial macrovessel in her right eye with an associated macroaneurysm. Both cases demonstrated an intricate capillary network in the central macula best visualized on optical coherence tomography angiography. Conclusion: Macroaneurysms can occur on both arterial and venous macrovessels. After rupture of these lesions, hemorrhage and exudation can resolve with observation alone. Macrovessels can also present with microaneurysms. Optical coherence tomography angiography can effectively image the complex capillary network associated with these vascular anomalies. Abstract : Macroaneurysms can occur in the setting of congenital retinal macrovessels and these vascular anomalies, along with an extensive central capillary network can be successfully visualized using optical coherence tomography angiography. Macrovessels can also harbor a series of microaneurysms in their vicinity.